Case report: Endolymphatic sac tumor with blurred vision - Yuan, Ke; Luo, Weijian; Chen, Jia; Peng, Quanzhou; Tong, Xiaoguang; Hu, Jiliang (Frontiers in Oncology, 2025)
IntroductionEndolymphatic sac tumor (ELST) is a rare neoplasm that exhibits aggressive growth primarily in the endolymphatic capsule and can potentially affect nearby neurovascular structures. The diagnosis of ELST poses challenges due to its low prevalence, gradual progression, and nonspecific symptomatology. It is currently believed that prompt surgical intervention is recommended for endolymphatic sac tumors upon diagnosis. In cases where the lesion is complex or in close proximity to vital blood vessels and nerves, making complete resection challenging, adjuvant therapy may be employed postoperatively. This approach aims to enhance treatment outcomes.Case presentationA case of a 53-year-old male was admitted to the Department of Neurosurgery of Shenzhen People’s Hospital with the main cause of dizziness and blurred vision, and was found to have an occupation in the pontocerebellar angle for about 20 days. Preoperative cranial CT suggested that the temporal bone mastoid was widely damaged with worm-like bone, and some of them showed honeycomb changes. MRI suggested that shadow was seen in the posterior part of the left internal auditory canal, temporal bone mastoid and jugular foramen, with a size of about 28x21x27mm.The T1-weighted image showed low and equal signals, and the T2-weighted image showed equal and slightly low signals in the center with multicompartmental cystic high signals in the margin. The center of the mass strengthened significantly after enhancement. The patient had no other clinical manifestations and no family history. The clinical diagnosis was left-sided pontocerebellar angle occupation - nature to be determined. The occupation was resected microscopically using the distal lateral combined anterior approach to the sigmoid sinus. Due to the extremely rich blood supply of the tumor, the tumor was embedded in the petrous humerus, which was soft and tough, and the surrounding structures were not clearly displayed, making surgical resection extremely difficult. postoperative pathology and immunohistochemistry confirmed that this lesion was an endolymphatic cystic tumor. After surgery, most of the tumor was successfully resected while preserving neurological function well, and the residual tumor was treated with adjuvant gamma knife with good results.ConclusionELST is a rare, low-grade, locally aggressive tumor that is difficult to diagnose early. During the surgery, it was observed that the tumor had a significant blood supply, which made its removal challenging. Preoperative embolization of the tumor’s blood supply artery would facilitate surgical resection and help avoid massive intraoperative bleeding. Complete surgical resection is the treatment of choice, and any remaining tumor remnants can be managed with adjuvant radiotherapy post-surgery, necessitating long-term follow-up to monitor any developments.